The impact of diabetes on short-, intermediate- and long-term mortality following left ventricular assist device implantation. (11th January 2022) - Kogan, Alexander; Frogel, Jonathan; Ram, Eilon; Jamal, Tamer; Peled-Potashnik, Yael; Maor, Elad; Grupper, Avishay; Morgan, Avi; Segev, Amit; Raanani, Ehud; Sternik, Leonid
Abstract: OBJECTIVES: Type 2 diabetes mellitus (DM) is a frequent comorbidity among patients suffering from advanced heart failure necessitating a left ventricular assist device (LVAD) implant. The goal of this study was to evaluate the impact of type 2 DM on early and long-term outcomes of patients following an LVAD implant. METHODS: We performed an observational cohort study in a large tertiary care centre in Israel. All data of patients who underwent a continuous flow LVAD implant between 2006 and 2020 were extracted from our departmental database. Patients were divided into 2 groups: group I (patients without diabetes) and group II (patients with diabetes). We compared short-term (30-day and 3-month) mortality, intermediate-term (1- and 3-year) mortality and long-term (5 year) mortality between the 2 groups. RESULTS: The study population included 154 patients. Group I (patients without diabetes) comprised 88 patients and group II (patients with diabetes) comprised 66 patients. The mean follow-up duration was 38.2 ± 30.3 months. Short- and intermediate-term mortality (30 days, 1 year and 3 years) was higher in the group with DM compared with the group without DM but did not reach any statistically significant difference: 16.1% vs 9.8% ( P = 0.312), 24.2% vs 17.3% ( P = 0.399) and 30.6% vs 21.9% ( P = 0.127) respectively. Long-term 5-year mortality was significantly higher in the group with DM compared to the group without: 38.7% vs 24.4% ( P = 0.038). Furthermore, predictors of long-term mortality included diabetes (hazard ratio 2.09, confidence interval 1.34–2.84, P = 0.004), as demonstrated by regression analysis. CONCLUSIONS: Patients with diabetes and those without diabetes have similar 30-day and short- and intermediate-term mortality rates. The mortality risk of diabetic patients begins to increase 3 years after an LVAD implant. Diabetes is an independent predictor of long-term, 5-year mortality after an LVAD implant. Clinical trial registration: Ethical Committee of Sheba Medical Centre, Israel, on 2 December 2014, Protocol 4257. Abstract : Congestive heart failure is a serious disease with profound effects on functional status, quality of life and survival.